IMPROVING THE RELIABILITY OF THE OF GROSS REGIONAL PRODUCT ESTIMATION WITHIN THE FRAMEWORK OF REGIONAL FORECASTS - O. Karasev I.; V. Kondrat'eva I.; N. Mikheeva N.; T. Shinkarenko V.; Олег Карасев Игоревич; В. Кондратьева И.; Н. Михеева Н.; Т. Шинкаренко В. (Information and publishing center "Statistics of Russia", 2017)
The article describes the role of the gross regional product (GRP) in the scenario forecasting of regional economy development using the pilot region - Sakha (Yakutia) Republic - as an example. The special attention is paid to the compatibility of statistical information obtained at the federal and regional levels in order to ensure the consistency of relevant forecasts. The scope and direction of gross regional product changes were estimated with regard to the transition to new GRP methodology due to the recalculations of the System of National Accounts (SNA) indicators for 2011-2014 at the federal level launched by the Federal State Statistics Service (Rosstat) in 2015. The results of the experimental correction of GRP according to the new methodology, which are necessary for the forecast of the Republic of Sakha (Yakutia) socio-economic development for the period of up to 2035 in accordance with the scenarios - basic, conservative and targetoriented, - are presented. The recalculation of the Sakha (Yakutia) Republic' GRP physical volume dynamics under each scenario has been made taking into account the expected methodological changes. В статье отражена роль показателя валового регионального продукта (ВРП) при построении сценарных прогнозов развития региональной экономики на примере «пилотного» региона - Республика Саха (Якутия). Авторы особое внимание уделяют проблеме сопоставимости статистической информации, полученной на федеральном и региональном уровнях, что определяется необходимостью согласования соответствующих прогнозных построений. Представлена оценка масштабов и направлений возможного изменения валового регионального продукта при переходе на новую методологию его исчисления ввиду проведенных в 2015 г. Федеральной службой государственной статистики (Росстат) пересчетов показателей системы национальных счетов (СНС) за 2011-2014 гг. на федеральном уровне. Описаны результаты экспериментального пересчета ВРП по новой методике, которые являются необходимыми для целей построения прогноза социально-экономического развития Республики Саха (Якутия) на период до 2035 г. в соответствии с предложенными сценариями: базовым, консервативным и целевым. Проведена корректировка динамики физического объема ВРП Республики Саха (Якутия) по сценариям с учетом изменения методологии расчета ВРП.